ROCK MUSIC AND NATIONAL IDENTITY IN HUNGARY - Milun, Kathryn (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1991)
Marxism and nationalism. The political form and meaning of the discourse of national identity in Hungary as it appears in popular culture. Hungarian rock and shamanpunk. The debate over the national flag.